THE INFLUENCE OF FINANCIAL DISTRESS, COMPANY CHARACTERISTIC AND CORPORATE GOVERNANCE ON VOLUNTARY DISCLOSURE IN AN ANNUAL REPORT - Putri, Yolanda Gusvia (ACCOUNTABILITY, 2020)
This study aims to examine the influence of the financial distress, profitability, liquidity, firm size, commissioners and audit committee on voluntary disclosure in the annual report of manufacturing companies listed on Indonesia Stock Exchange over period of 2012 to 2016. The population of this study is manufacturing companies listed on Indonesia Stock Exchange. There are 33 manufacturing companies that fit the criteria. After filtering the companies using the purposive sampling method, there are 14 manufacturing companies used in this study. The results of the study show that: (1) financial distress does not have any significant influence on voluntary disclosure; (2) profitability does not have any significant influence on voluntary disclosure; (3) liquidity does not have any significant influence on to voluntary disclosure; (4) firm size does not have any significant influence on voluntary disclosure; (5) the audit committee does not have any significant influence on voluntary disclosure; and (6) the board of commissioners has a significant influence on voluntary disclosure.